Chitosan inhibits septin‐mediated plant infection by the rice blast fungus Magnaportheoryzae in a protein kinase C and Nox1 NADPH oxidase‐dependent manner. Issue 4 (17th March 2021) - Lopez‐Moya, Federico; Martin‐Urdiroz, Magdalena; Oses‐Ruiz, Miriam; Were, Vincent M.; Fricker, Mark D.; Littlejohn, George; Lopez‐Llorca, Luis V.; Talbot, Nicholas J.
Summary: Chitosan is a partially deacetylated linear polysaccharide composed of β‐1, 4‐linked units of d ‐glucosamine and N‐acetyl glucosamine. As well as a structural component of fungal cell walls, chitosan is a potent antifungal agent. However, the mode of action of chitosan is poorly understood. Here, we report that chitosan is effective for control of rice blast disease. Chitosan application impairs growth of the blast fungus Magnaporthe oryzae and has a pronounced effect on appressorium‐mediated plant infection. Chitosan inhibits septin‐mediated F‐actin remodelling at the appressorium pore, thereby preventing repolarization of the infection cell. Chitosan causes plasma membrane permeabilization of M. oryzae and affects NADPH oxidase‐dependent synthesis of reactive oxygen species, essential for septin ring formation and fungal pathogenicity. We further show that toxicity of chitosan to M. oryzae requires the protein kinase C‐dependent cell wall integrity pathway, the Mps1 mitogen‐activated protein kinase and the Nox1 NADPH oxidase. A conditionally lethal, analogue (PP1)‐sensitive mutant of Pkc1 is partially remediated for growth in the presence of chitosan, while ∆nox1 mutants increase their glucan : chitin cell wall ratio, rendering them resistant to chitosan. Taken together, our data show that chitosan is a potent fungicide which requires the cell integrity pathway, disrupts plasma membrane function and inhibits septin‐mediated plant infection.